Self-healing high-toughness concrete material and preparation method and application thereof
Patent Information
- Application Number
- CN202611400043.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
表面封护、灌浆、碳纤维补强均属于事后被动修复,无法提前遏制微裂缝发展;微胶囊、渗透结晶等自修复材料在高水压、动水环境下修复失效
本发明提供了一种自愈合高韧性混凝土材料,通过各原料配合作用,既可以实现裂缝的自主愈合,又可大幅度提升材料的抗冲击、抗冻融及抗渗耐久性能,适用水工高水压和动水冲刷环境。其中,硅酸盐水泥提供强度骨架;粉煤灰和硅灰用于改善材料韧性及界面密实度;吸水树脂作为内养护剂和愈合剂,可降低浆体早期收缩并为后期裂缝愈合提供水分;乳胶通过形成柔性聚合物膜,优化纤维-基体界面粘结,提高材料韧性和抗渗性;甲酸钙加速水泥水化,提高早期强度并抑制塑性裂缝;细骨料改善流动性并降低造价;减水剂保证浆体流动性,利于纤维分散;PE纤维作为增强相,通过桥接裂缝实现应变硬化与多缝开裂,将材料由脆性破坏转变为高延性破坏。
Smart Images

Figure SMS_1 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydraulic structure technology, specifically relating to a self-healing high-toughness concrete material, its preparation method, and its application. Background Technology
[0002] Concrete hydraulic structures such as dams, levees, and aqueducts are subjected to multiple loads over long periods, including scouring by flowing water, high water pressure, freeze-thaw cycles, and uneven foundation settlement. Concrete itself has low tensile strength, and during construction and service, it is prone to generating numerous micro-cracks that are difficult to detect during inspections. As these cracks continue to expand and penetrate, they form leakage channels, leading to steel corrosion and matrix erosion, significantly reducing the structure's load-bearing capacity, and in severe cases, inducing major safety accidents such as dam failure.
[0003] Currently, hydraulic engineering crack treatment solutions fall into two categories: traditional repair materials and self-healing concrete. Surface sealing, grouting, and carbon fiber reinforcement are all reactive repairs that cannot prevent the development of microcracks in advance. Self-healing materials such as microcapsules and penetrating crystallization fail to repair under high water pressure and dynamic water conditions. Existing technologies lack a multi-component synergistic compound system, making it difficult to simultaneously achieve self-healing of cracks and improvements in material impact resistance, freeze-thaw resistance, and impermeability durability. Consequently, their overall performance is not suitable for the long-term, harsh service environment of hydraulic engineering projects. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the purpose of this invention is to provide a self-healing high-toughness concrete material, its preparation method, and its application.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] A first typical embodiment of the present invention provides a self-healing, high-toughness concrete material, the raw materials for which are prepared by weight parts include: 30-120 parts silicate cement, 30-60 parts fly ash, 10-60 parts silica fume, 0.1-3 parts water-absorbing resin, 2-20 parts latex, 1-10 parts calcium formate, 40-120 parts fine aggregate, 25-60 parts water, PE fiber, water-reducing agent. The volume of PE fibers is 0.5-2.5% of the volume of self-healing high-toughness concrete materials; The water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume.
[0007] A second aspect of the present invention provides a method for preparing the self-healing high-toughness concrete material described in the first aspect, comprising: Silicate cement, fly ash, silica fume, water-absorbing resin, latex, calcium formate, and fine aggregate are mixed to obtain a mixed dry material; Mix the water-reducing agent with 80-90% of the total water volume and then add it to the mixed dry material. Stir well to obtain the slurry. Adjust the slump spread of the slurry to 150-250 mm with the remaining water, add PE fibers in batches, and stir to obtain a self-healing high-toughness concrete material.
[0008] A third aspect of the present invention provides an application of the self-healing, high-toughness concrete material described in the first aspect in the repair of cracks in hydraulic structures.
[0009] The beneficial effects of this invention are as follows: This invention provides a self-healing, high-toughness concrete material. Through the combined action of various raw materials, it can achieve self-healing of cracks and significantly improve the material's impact resistance, freeze-thaw resistance, and impermeability durability, making it suitable for high-pressure hydraulic engineering environments and dynamic water erosion environments. Specifically, silicate cement provides the strength framework; fly ash and silica fume improve the material's toughness and interfacial density; water-absorbing resin acts as an internal curing agent and healing agent, reducing early shrinkage of the slurry and providing moisture for later crack healing; latex forms a flexible polymer film, optimizing fiber-matrix interfacial bonding and improving the material's toughness and impermeability; calcium formate accelerates cement hydration, increases early strength, and inhibits plastic cracking; fine aggregate improves fluidity and reduces costs; water-reducing agent ensures slurry fluidity and facilitates fiber dispersion; and PE fiber, as a reinforcing phase, bridges cracks to achieve strain hardening and multi-crack propagation, transforming the material from brittle failure to high-ductility failure. Detailed Implementation
[0010] Given that existing hydraulic concrete is prone to developing hidden microcracks, traditional repair methods can only provide post-treatment solutions. Conventional self-healing materials exhibit poor self-healing performance under high water pressure and dynamic water erosion conditions, and lack a multi-component synergistic compounding system, failing to simultaneously achieve self-healing of cracks and improved comprehensive durability performance in terms of impact resistance, freeze-thaw resistance, and impermeability. Therefore, this invention proposes a self-healing high-toughness concrete material, its preparation method, and its application. This invention constructs a multi-raw material synergistic compounding self-healing high-toughness concrete system. A basic strength matrix is formed by compounding silicate cement, fly ash, and silica fume. Modified superabsorbent resin, dispersible latex, and calcium formate are used to synergistically regulate matrix shrinkage, interfacial bonding, and early plastic cracks. Simultaneously, a specific volumetric dosage of PE fiber is introduced as a reinforcing phase, supplemented with Yellow River sand and a water-reducing agent to optimize construction performance and production costs. The components work together and complement each other. On the one hand, the water-absorbing resin provides the moisture needed for self-healing, the latex optimizes the interface bonding to enhance the self-healing effect, and the calcium formate reduces the original plastic cracks, so as to achieve long-term self-healing of cracks. On the other hand, the PE fiber plays a bridging and toughening role, transforming the brittle failure mode of concrete. The overall material's impact resistance, freeze-thaw resistance, impermeability and durability are improved simultaneously, resulting in concrete materials that are suitable for the complex and harsh service environment of hydraulic engineering. This effectively controls the development of micro-cracks from the source and ensures the long-term safe operation of hydraulic structures.
[0011] In a first aspect, the present invention provides a self-healing, high-toughness concrete material, wherein the raw materials for preparation, by weight, comprise: 30-120 parts silicate cement, 30-60 parts fly ash, 10-60 parts silica fume, 0.1-3 parts water-absorbing resin, 2-20 parts latex, 1-10 parts calcium formate, 40-120 parts fine aggregate, 25-60 parts water, PE fiber, water-reducing agent. The volume of PE fibers is 0.5-2.5% of the volume of self-healing high-toughness concrete materials; The water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume.
[0012] This invention provides a self-healing, high-toughness concrete material that can be automatically triggered and continuously responded to in the early stage of microcrack initiation in hydraulic structures, and can adapt to underwater high humidity, high pressure and water flow scouring environments.
[0013] In this invention, the superabsorbent resin is a hydrophobically modified polyacrylic acid superabsorbent resin. By performing surface crosslinking and hydrophobic modification on commercial superabsorbent resin, its water absorption and retention performance, salt resistance, and slow-release characteristics are improved in high water pressure and high ion concentration environments in hydraulic engineering. This allows it to act as an internal protective agent to inhibit shrinkage cracks in the early stages, and to continuously release moisture after cracks appear to promote subsequent self-healing reactions.
[0014] In this invention, the preparation method of the hydrophobically modified polyacrylic acid water-absorbing resin includes: The polyacrylic water-absorbing resin was dried until its moisture content was less than 0.5%. Prepare a crosslinking agent solution, spray the crosslinking agent solution onto the surface of polyacrylic acid water-absorbing resin, stir, and react at 800-100℃ for 1-2 h to obtain surface crosslinked modified water-absorbing resin; Prepare a hydrophobic modification solution, spray the hydrophobic modification solution onto the surface of the cross-linked modified water-absorbing resin, stir, and dry to obtain a hydrophobic modified polyacrylic acid water-absorbing resin.
[0015] In this invention, the particle size of the polyacrylic acid-based superabsorbent resin is 80-150 mesh. The polyacrylic acid-based superabsorbent resin includes, but is not limited to, any one of sodium polyacrylate or potassium polyacrylate.
[0016] In this invention, the crosslinking agent solution comprises, by mass parts: 0.5-2.0 parts of ethylene glycol diglycidyl ether, 10-20 parts of water, and 5-10 parts of anhydrous ethanol; the mass ratio of the crosslinking agent solution to the polyacrylic acid-based water-absorbing resin is 15.5-32:100.
[0017] In this invention, the crosslinking agent solution comprises, by mass parts: 1.0 part of ethylene glycol diglycidyl ether, 15 parts of water, and 7.5 parts of anhydrous ethanol; the mass ratio of the crosslinking agent solution to the polyacrylic acid-based superabsorbent resin is 23.5:100.
[0018] In this invention, the crosslinking agent solution is uniformly sprayed onto the surface of polyacrylic water-absorbing resin under high-speed stirring in an atomized spraying manner for 5-10 minutes. After spraying, stirring is continued for 15-20 minutes to ensure that the crosslinking agent is uniformly coated on the resin surface.
[0019] In this invention, the hydrophobic modified solution comprises, by mass parts: 1-3 parts calcium stearate, 20-40 parts anhydrous ethanol, and 5-10 parts water; the mass ratio of the hydrophobic modified solution to the polyacrylic acid-based water-absorbing resin is 26-53:100.
[0020] In this invention, the hydrophobic modification solution is sprayed uniformly onto the surface of the surface crosslinked modified water-absorbing resin in an atomized manner, stirred and mixed for 20-30 minutes, and dried to form a uniform hydrophobic film of calcium stearate on the resin surface. The resulting surface crosslinked modified water-absorbing resin is passed through a 100-mesh standard sieve to remove a small amount of agglomerated particles generated during the modification process, and the final hydrophobic modified polyacrylic acid water-absorbing resin product is obtained and sealed in moisture-proof packaging for later use.
[0021] In this invention, the particle size of the hydrophobic modified polyacrylic water-absorbing resin is less than or equal to 0.15 mm.
[0022] In this invention, the latex comprises vinyl acetate-ethylene copolymer (VAE) with a particle size range of 80-100 μm, an ash content of 8-12%, a pH of 5-8, and a bulk density of 400-600 kg / m³. 3 .
[0023] In this invention, the fine aggregate comprises, by mass parts: 100 parts activated modified Yellow River sand, 3-8 parts fly ash microspheres, and 0.5-1.0 parts nano silica; the particle size of the fly ash microspheres is ≤5 μm.
[0024] In this invention, the preparation method of the fine aggregate includes: mixing activated modified Yellow River sand, fly ash microspheres, and nano-silica for 30-40 minutes, so that ultrafine mineral particles are uniformly coated on the surface of Yellow River sand particles, filling surface micropores and depressions to form a dense composite particle structure. This treatment can significantly improve the density of the aggregate-slurry interface transition zone and enhance the interfacial bonding strength.
[0025] Yellow River sand is the fine aggregate selected in this invention to reduce costs and achieve solid waste resource utilization. However, due to the rough surface of Yellow River sand particles, high mud content, and uneven gradation, direct use would increase water consumption and weaken the strength of the interfacial transition zone. Therefore, this invention provides a systematic pretreatment process that optimizes particle size distribution, improves surface properties, and introduces active micro-powders to ensure that its performance meets the high standards required for aggregates in high-toughness concrete.
[0026] In this invention, the method for preparing the activated and modified Yellow River sand includes: Prepare a surface activation treatment solution, spray the solution onto the surface of Yellow River sand, stir, and dry to obtain the final product.
[0027] In this invention, the particle size distribution of the Yellow River sand includes 15-25% 0.075-0.3 mm, 30-40% 0.3-0.6 mm, 25-35% 0.6-1.18 mm, and 5-15% 1.18-2.36 mm, by mass percentage. The Yellow River sand is a compounded Yellow River sand, and its fineness modulus is determined using the continuous gradation method, controlling the fineness modulus to be 2.3-2.8. The gradation curve meets the requirements for medium sand in Zone II of GB / T14684-2022 "Construction Sand".
[0028] In this invention, the surface activation treatment solution comprises, by mass parts: 0.5-1.5 parts of silane coupling agent, 30-50 parts of water, 50-70 parts of anhydrous ethanol, and a pH of 4.0-5.0.
[0029] In this invention, the surface activation treatment liquid is sprayed evenly onto the surface of Yellow River sand in an atomized manner, stirred and mixed for 15-20 minutes, and then dried to allow the coupling agent to form chemical bonds on the surface of the sand particles.
[0030] In this invention, the amount of surface activation treatment liquid used is 2-5% of the mass of Yellow River sand, specifically 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0031] This invention selects polyethylene fiber as the reinforcing phase, which possesses excellent mechanical properties and chemical stability. However, PE fibers have a smooth surface and are chemically inert, resulting in weak interfacial adhesion with the cement matrix, making it difficult to fully exert their bridging and toughening effect. Therefore, this invention optimizes the PE fibers used, preferably modified PE fibers. This invention significantly improves the surface roughness and surface energy of the PE fibers through a combination of plasma etching and chemical grafting, enhancing the chemical bonding and mechanical anchoring effect at the fiber-matrix interface.
[0032] In this invention, the method for preparing the modified PE fiber includes: Select polyethylene fibers with a diameter of 20-40 μm and a length of 12-18 mm, clean the surface, dry, and set aside. The cleaned and dried polyethylene fibers were subjected to plasma etching to obtain plasma-activated polyethylene fibers. A grafting reaction solution was prepared, and plasma-activated polyethylene fibers were immersed in the grafting reaction solution to carry out the reaction. After the reaction was completed, the fibers were removed, washed, and dried to obtain modified PE fibers.
[0033] In this invention, the plasma etching process includes: evacuating to a vacuum level ≤ 5 Pa, introducing argon gas as the working gas at a flow rate of 50-100 mL / min, and adjusting the vacuum chamber pressure to 20-50 Pa; turning on the radio frequency power supply and setting the power to 100-200 W, and performing plasma etching on the cleaned and dried polyethylene fiber for a processing time of 2-8 min; after the processing is completed, maintaining the vacuum state and cooling for 10-15 min, and then removing the fiber for later use.
[0034] In this invention, the grafting reaction solution comprises, by mass parts: 3-8 parts acrylic acid, 0.1-0.3 parts N,N'-methylenebisacrylamide, 0.2-0.5 parts ammonium persulfate, 90-96 parts water, and a pH of 6.0-7.0.
[0035] In this invention, the step of immersing plasma-activated polyethylene fibers in a grafting reaction solution for reaction includes: adding plasma-activated polyethylene fibers to the grafting reaction solution and reacting at 60-80°C for 1-3 hours, stirring at a speed of 60-80 r / min during the reaction; after the reaction is completed, removing the fibers, washing, drying, opening, and cutting to obtain modified PE fibers.
[0036] In this invention, the length of the modified PE fiber is 12-18 mm, specifically 12 mm, 15 mm, 18 mm, etc.
[0037] In this invention, the raw materials for preparing the self-healing high-toughness concrete material, by weight, include: The composition includes 30-40 parts silicate cement, 50-60 parts fly ash, 10-20 parts silica fume, 0.1-3 parts water-absorbing resin, 2-10 parts latex, 1-5 parts calcium formate, 40-50 parts fine aggregate, 25-30 parts water, PE fiber, and water-reducing agent. The volume of PE fiber is 1.0-2.5% of the volume of the self-healing high-toughness concrete material. The mass of the water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume. Within this range, the self-healing high-toughness concrete material exhibits excellent mechanical properties and self-healing efficiency.
[0038] In this invention, the raw materials for preparing the self-healing high-toughness concrete material, by weight, include: The self-healing high-toughness concrete material comprises 30-40 parts silicate cement, 50-60 parts fly ash, 10-20 parts silica fume, 0.3-1 part superabsorbent polymer, 2-10 parts latex, 1-5 parts calcium formate, 40-50 parts fine aggregate, 25-30 parts water, PE fiber, and water-reducing agent. The volume of PE fiber is 1.5-2.0% of the volume of the self-healing high-toughness concrete material. The mass of the water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume. Within this range, the 28-day compressive strength of the self-healing high-toughness concrete material is ≥42.3 MPa, and the crack healing rate is ≥82.4%, which can meet the dual requirements of hydraulic structures for material load-bearing capacity and self-repair function.
[0039] In this invention, the synergistic effect of various raw materials improves the overall performance of concrete materials. Specifically, silicate cement provides the strength framework; fly ash and silica fume improve the material's toughness and interfacial density; modified superabsorbent resin acts as an internal curing agent and healing agent, reducing early shrinkage of the slurry and providing moisture for later crack healing; dispersible latex optimizes fiber-matrix interfacial bonding by forming a flexible polymer film, improving the material's toughness and impermeability and significantly enhancing the self-healing ability of cracks; calcium formate accelerates cement hydration, improves the early strength of concrete, and inhibits plastic cracks, providing a stable early matrix environment for crack self-healing; pretreated Yellow River sand, as fine aggregate, improves the fluidity of freshly mixed slurry, replacing quartz sand and reducing costs; water serves as the hydration reaction medium, affecting the material's strength, porosity, and fiber dispersion; a water-reducing agent ensures slurry fluidity, guaranteeing uniform fiber dispersion and high density; and modified PE fibers, as a reinforcing phase, bridge cracks to achieve strain hardening and multi-crack opening, transforming the material from brittle failure to highly ductile failure.
[0040] A second typical embodiment of the present invention provides a method for preparing the self-healing high-toughness concrete material, comprising: Silicate cement, fly ash, silica fume, water-absorbing resin, latex, calcium formate, and fine aggregate are mixed to obtain a mixed dry material; Mix the water-reducing agent with 80-90% of the total water volume and then add it to the mixed dry material. Stir well to obtain the slurry. Adjust the slump spread of the slurry to 150-250 mm with the remaining water, add PE fibers in batches, and stir to obtain a self-healing high-toughness concrete material.
[0041] This invention combines various component materials according to a specific feeding sequence and mixing regime to prepare a self-healing high-toughness concrete material suitable for hydraulic structures, which has both strain hardening characteristics and crack self-healing function.
[0042] In this invention, silicate cement, fly ash, silica fume, water-absorbing resin, latex, calcium formate and fine aggregate are stirred at a speed of 20±5 r / min for 3-5 min to obtain a mixed dry material; Mix the water-reducing agent with 80-90% of the total water volume and add it to the mixed dry material. Stir at 45-60 r / min for 2-3 min to obtain the slurry. Adjust the slump spread of the slurry to 150-250 mm with the remaining water, add PE fibers in batches and stir. After all the PE fibers have been added, stir at a speed of 45-60 r / min for 2-3 min to obtain a self-healing high-toughness concrete material. The resulting self-healing high-toughness concrete material was poured, compacted by vibration, and then cured after surface polishing.
[0043] In this invention, the method for preparing the self-healing high-toughness concrete material includes: I. Modification Treatment of Superabsorbent Polymers Step 1: Raw material selection and pre-drying.
[0044] Select polyacrylic superabsorbent resin with a particle size of 80-150 mesh as the matrix material (including sodium polyacrylate and potassium polyacrylate); place the superabsorbent resin in a forced-air drying oven and dry it at a constant temperature of 50-60℃ for 4-6 hours until the moisture content is less than 0.5%; then cool it to room temperature and seal it for storage for later use.
[0045] Step 2: Surface crosslinking modification treatment.
[0046] First, prepare a surface crosslinking agent solution, which consists of the following components: 0.5-2.0 parts ethylene glycol diglycidyl ether, 10-20 parts water, and 5-10 parts anhydrous ethanol. Second, take 100 parts (by weight) of the dried superabsorbent resin obtained in step 1 and place it in a high-speed mixer. Finally, uniformly spray the surface crosslinking agent solution onto the surface of the superabsorbent resin under high-speed stirring using a mist spraying method for 5-10 minutes. After spraying, continue stirring for 15-20 minutes to ensure the crosslinking agent is uniformly coated on the resin surface.
[0047] The superabsorbent resin coated with the crosslinking agent was transferred to a constant-temperature reactor and reacted in a sealed environment at 80-100℃ for 1-2 hours. This allowed the surface crosslinking agent to undergo esterification and crosslinking with the carboxyl groups on the surface molecular chains of the resin, forming a dense surface crosslinked layer. After the reaction was complete, the mixture was allowed to cool naturally to room temperature.
[0048] Step 3: Hydrophobic surface modification.
[0049] Take the surface-crosslinked modified superabsorbent resin obtained in step 2 and put it back into the high-speed mixer. Prepare a hydrophobic modification solution, which comprises: 1-3 parts calcium stearate, 20-40 parts anhydrous ethanol, and 5-10 parts water. Spray the hydrophobic modification solution evenly onto the surface of the surface-crosslinked modified superabsorbent resin in a misting manner, and stir and mix for 20-30 minutes. Then transfer the material to an oven and dry it at 60-70℃ for 2-3 hours to form a uniform hydrophobic film of calcium stearate on the resin surface.
[0050] Step 4: Screening and Packaging.
[0051] The modified superabsorbent resin obtained in step 3 is passed through a 100-mesh standard sieve to remove a small amount of agglomerated particles generated during the modification process, and the final modified superabsorbent resin product is obtained. It is then sealed and packaged in a moisture-proof container for later use.
[0052] II. Pretreatment of Yellow River Sand Step 1: Initial screening and drying of raw materials.
[0053] The excavated Yellow River sand is naturally air-dried until the moisture content is below 3%, and then fed into a drum dryer and dried at 105-110℃ until the moisture content is below 0.5%. The dried Yellow River sand is then fed into a vibrating screen and passed through 2.36 mm and 1.18 mm square hole screens in sequence to remove gravel, shell fragments and organic impurities with a particle size greater than 2.36 mm, retaining fine aggregate components with a particle size range of 0.075-2.36 mm.
[0054] Step 2: Particle shaping and gradation optimization.
[0055] The screened Yellow River sand obtained in step 1 is fed into a vertical impact crusher (sand making machine) for particle shaping. The rotor linear velocity is controlled at 40-60 m / s, and the processing time is 3-5 min, so that the particle edges are moderately rounded and the particle morphology is improved. After shaping, the material is fed into an air classifier for air classification, collecting four groups of fine materials with particle sizes in the ranges of 0.075-0.3 mm, 0.3-0.6 mm, 0.6-1.18 mm, and 1.18-2.36 mm.
[0056] The aggregate was blended according to the following mass ratios: 15-25% for the 0.075-0.3 mm range, 30-40% for the 0.3-0.6 mm range, 25-35% for the 0.6-1.18 mm range, and 5-15% for the 1.18-2.36 mm range. After blending, the fineness modulus was determined using the continuous gradation method, controlling it to be 2.3~2.8. The gradation curve met the requirements for medium sand in Zone II of GB / T 14684 "Construction Sand".
[0057] Step 3: Surface activation treatment.
[0058] Prepare a surface activation treatment solution, comprising, by mass, 0.5-1.5 parts of silane coupling agent (KH-550), 30-50 parts of water, and 50-70 parts of anhydrous ethanol. Adjust the pH to 4.0-5.0 with glacial acetic acid and hydrolyze for 30 minutes. Add the optimized Yellow River sand obtained in step 2 to a horizontal mixer. While stirring, uniformly spray the activation treatment solution onto the sand surface using an atomizing method. The amount of treatment solution used is 2-5% of the sand mass. Mix for 15-20 minutes. Subsequently, dry the material at 80-90℃ for 1-2 hours to allow the coupling agent to form chemical bonds on the sand particle surface.
[0059] Step 4: Composite treatment with ultrafine mineral fillers.
[0060] Take 100 parts of activated Yellow River sand obtained in step 3, add 3-8 parts of ultrafine fly ash microspheres (particle size ≤ 5 μm) and 0.5-1.0 parts of nano SiO2, and mix them in a V-type mixer for 30-40 min so that the ultrafine mineral particles are evenly coated on the surface of the Yellow River sand particles, filling the surface micropores and depressions to form a dense composite particle structure.
[0061] III. Modification Treatment of PE Fibers Step 1: Clean the fiber surface.
[0062] High-strength, high-modulus polyethylene fibers with a diameter of 20-40 μm and a length of 12-18 mm were selected and immersed in acetone solution. The fibers were then ultrasonically cleaned for 15-20 minutes to remove residual oil, release agent, and other organic contaminants from the fiber surface. After removal, the fibers were rinsed repeatedly with deionized water 3-5 times and dried in a 60℃ oven until constant weight.
[0063] Step 2: Low-temperature plasma treatment.
[0064] The clean, dry PE fibers obtained in step 1 are evenly laid in the vacuum chamber of the plasma treatment equipment, and the vacuum is evacuated to a background vacuum level ≤ 5 Pa. High-purity argon gas is introduced as the working gas, with a flow rate controlled at 50-100 mL / min, and the vacuum chamber pressure is adjusted to 20-50 Pa. The radio frequency power supply is turned on, and the power is set to 100-200 W to perform plasma etching treatment on the fibers for 2-8 min. During the treatment, high-energy argon ions bombard the fiber surface, producing a dual effect of physical etching and chemical activation, introducing active functional groups such as hydroxyl and carbonyl groups, and simultaneously creating a micro-nano-scale rough structure on the fiber surface. After the treatment, the fibers are cooled under vacuum for 10-15 min and then removed for later use.
[0065] Step 3: Chemical grafting modification.
[0066] Take the plasma-activated PE fiber obtained in step 2 and immediately immerse it in the grafting reaction solution for grafting treatment. The grafting reaction solution comprises, by mass parts: 3-8 parts acrylic acid, 0.1-0.3 parts N,N'-methylenebisacrylamide (crosslinking agent), 0.2-0.5 parts ammonium persulfate (initiator), and 90-96 parts water, with the pH adjusted to 6.0-7.0 using a 1 mol / L sodium hydroxide solution.
[0067] Activated PE fibers were added to the grafting reaction solution at a bath ratio of 1:30-50 (fiber mass:reaction liquid volume, g:mL). The reaction was carried out in a constant temperature water bath at 60-80℃ for 1-3 hours, with slow stirring at 60-80 r / min to ensure uniform grafting reaction. After the reaction was completed, the fibers were removed and washed repeatedly with large amounts of deionized water and ethanol to remove unreacted monomers and homopolymers.
[0068] Step 4: Drying and cutting.
[0069] The grafted modified PE fibers obtained in step 3 are dried in a vacuum drying oven at 50-60℃ until constant weight. The dried fiber bundles are then opened to disperse the fibers into monofilaments, and finally cut to the specified length (12-18 mm) to obtain the modified PE fiber product, which is then sealed and stored in a moisture-proof environment.
[0070] IV. Preparation of Self-Healing High-Toughness Concrete Step 1: Take materials and mix them.
[0071] Weigh the dry powders of silicate cement, fly ash, silica fume, latex, calcium formate, and modified superabsorbent polymer according to the specified proportions. Specifically: silicate cement: 40-120 parts; fly ash: 30-60 parts; silica fume: 30-60 parts; superabsorbent polymer: 0.1-10 parts; latex: 2-20 parts; calcium formate: 1-10 parts; fine aggregate: 40-120 parts.
[0072] Add the above powder materials together into a forced mixer and mix at low speed (20±5 r / min) for 3-5 minutes to ensure uniform mixing. Low-speed mixing avoids high shear forces that could damage the particle shape of the dispersible latex powder.
[0073] Step 2: Premix the water-reducing agent and stir once.
[0074] The polycarboxylate superplasticizer is premixed with 80-90% of the total water volume to obtain a premixed solution. During the mixing of the above powder materials, the premixed solution is slowly poured along the drum wall, and the mixer is started and stirred at medium speed (45-60 r / min) for 2-3 minutes to form a homogeneous slurry. The total water volume is 25-60 parts, and the superplasticizer is 0.5-1.0% of the mass of the cementitious material.
[0075] Step 3: Adjust the collapse spread.
[0076] Reserve 10-20% water for subsequent consistency adjustment, adjusting to a target slump spread of 150-250 mm. When adding water, add it slowly in 2-3 batches, stirring for 30 seconds after each addition, then stop the machine and measure until the target value is reached.
[0077] Step 4: Add PE fibers.
[0078] The weighed modified PE fibers are slowly and evenly added to the slurry obtained in step 3 in 3-5 batches, with an interval of about 30 seconds between each batch. Each batch is evenly spread back and forth along the axis of the mixer drum to avoid fixed-point addition. The amount added in each batch is limited to prevent the formation of a fiber accumulation layer on the slurry surface. The next batch is added only after the fibers from the previous batch have largely sunk below the slurry surface. The volume percentage of the modified PE fibers is approximately 0.5-2.5%.
[0079] Step 5: Mix.
[0080] After all the fibers are added, continue stirring at medium speed for 2-3 minutes until the fibers are evenly dispersed in the slurry and there are no visible clumps, thus obtaining freshly mixed self-healing high-toughness concrete.
[0081] Step 6: Pouring.
[0082] The freshly mixed self-healing high-toughness concrete obtained in step 5 is continuously and uniformly poured into the mold. A layered continuous pouring method is used, meaning the concrete is continuously poured from one end of the mold to the other, without skipping or jumping. The free fall height is controlled to not exceed 300mm to avoid fiber segregation caused by impact.
[0083] Step 7: Vibrate and compact.
[0084] Use a vibrating table or an external vibrator attached to the template for compaction. Control the amplitude to 0.3-0.5 mm and the vibration time to 10-20 seconds to densify the material and remove air bubbles. Closely observe the slurry surface during vibration; stop immediately when air bubbles have largely stopped being expelled and the surface is uniformly covered with slurry. Do not use immersion vibrators, as this will severely interfere with the uniform distribution of fibers.
[0085] Step 8: Surface polishing.
[0086] The surface of the compacted concrete is smoothed using a steel trowel.
[0087] Step 9: Early moisturizing and care.
[0088] Immediately after molding, the specimens should be covered with plastic film to prevent moisture evaporation, and cured for 24 hours. The covering should be directly attached to the concrete surface and not suspended in the air. After 24 hours, the specimens can be transferred to water for curing or allowed to cure naturally.
[0089] A third typical embodiment of the present invention provides an application of the self-healing high-toughness concrete material described above in the repair of cracks in hydraulic structures.
[0090] The self-healing, high-toughness concrete material provided by this invention possesses excellent mechanical properties. Testing showed that its 3 / 7 / 28-day compressive strength reached 28.6 / 38.2 / 52.4 MPa, respectively; for cracks with an initial width of approximately 102 μm, the healing rate reached 82.4% after 28 days of water curing.
[0091] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0092] The preparation methods of the hydrophobically modified polyacrylic acid water-absorbing resin, fine aggregate, and modified PE fiber used in the following examples and comparative examples are as follows: I. Preparation method of hydrophobically modified sodium polyacrylate water-absorbing resin: Step 1: Raw material selection and pre-drying.
[0093] A polyacrylic superabsorbent resin with a particle size of 100 mesh was selected as the matrix material (sodium polyacrylate). The superabsorbent resin was placed in a forced-air drying oven and dried at a constant temperature of 60°C for 6 hours until the moisture content was less than 0.5%. Then it was cooled to room temperature and sealed for storage for later use.
[0094] Step 2: Surface crosslinking modification treatment.
[0095] First, a surface crosslinking agent solution is prepared, comprising the following components: 1.0 part ethylene glycol diglycidyl ether, 15 parts water, and 7.5 parts anhydrous ethanol. Second, 100 parts (by weight) of the dried superabsorbent resin obtained in step 1 are placed in a high-speed mixer. Finally, the surface crosslinking agent solution is evenly sprayed onto the surface of the superabsorbent resin under high-speed stirring using a mist spraying method for 10 minutes. After spraying, stirring continues for 15 minutes to ensure the crosslinking agent is evenly coated on the resin surface.
[0096] The superabsorbent resin coated with the crosslinking agent was transferred to a constant-temperature reactor and reacted at 80°C for 1 hour in a sealed environment. This allowed the surface crosslinking agent to undergo an esterification crosslinking reaction with the carboxyl groups on the surface molecular chains of the resin, forming a dense surface crosslinked layer. After the reaction was completed, the mixture was allowed to cool naturally to room temperature.
[0097] Step 3: Hydrophobic surface modification.
[0098] Take the surface-crosslinked modified superabsorbent resin obtained in step 2 and put it back into the high-speed mixer. Prepare a hydrophobic modification solution, which comprises: 1 part calcium stearate, 20 parts anhydrous ethanol, and 10 parts water. Spray the hydrophobic modification solution evenly onto the surface of the surface-crosslinked modified superabsorbent resin in a misting manner and stir for 20 min. Then transfer the material to an oven and dry it at 60 °C for 3 h to form a uniform hydrophobic film of calcium stearate on the resin surface.
[0099] Step 4: Screening and Packaging.
[0100] The modified superabsorbent resin obtained in step 3 is passed through a 100-mesh standard sieve to remove a small amount of agglomerated particles generated during the modification process, and the final modified superabsorbent resin product, namely hydrophobic modified sodium polyacrylate superabsorbent resin, is obtained and sealed in moisture-proof packaging for later use.
[0101] II. Preparation method of fine aggregate: Step 1: Initial screening and drying of raw materials.
[0102] The excavated Yellow River sand is naturally air-dried until the moisture content is below 3%, and then fed into a drum dryer and dried at 105-110℃ until the moisture content is below 0.5%. The dried Yellow River sand is then fed into a vibrating screen and passed through 2.36 mm and 1.18 mm square hole screens in sequence to remove gravel, shell fragments and organic impurities with a particle size greater than 2.36 mm, retaining fine aggregate components with a particle size range of 0.075-2.36 mm.
[0103] Step 2: Particle shaping and gradation optimization.
[0104] The screened Yellow River sand obtained in step 1 is fed into a vertical impact crusher (sand making machine) for particle shaping. The rotor linear velocity is controlled at 40 m / s, and the processing time is 3 min, so that the particle edges are moderately rounded and the particle morphology is improved. After shaping, the material is fed into an air classifier for air classification, and four groups of fine materials with particle sizes in the ranges of 0.075-0.3 mm, 0.3-0.6 mm, 0.6-1.18 mm, and 1.18-2.36 mm are collected respectively.
[0105] The aggregate was blended according to the following mass ratios: 20% for the 0.075-0.3 mm range, 30% for the 0.3-0.6 mm range, 35% for the 0.6-1.18 mm range, and 15% for the 1.18-2.36 mm range. The fineness modulus was determined using the continuous gradation method after blending, and the fineness modulus was controlled to be 2.3~2.8. The gradation curve met the requirements for medium sand in Zone II of GB / T 14684 "Construction Sand".
[0106] Step 3: Surface activation treatment.
[0107] Prepare a surface activation treatment solution comprising, by mass, 1.0 part of silane coupling agent (KH-550), 30 parts of water, and 50 parts of anhydrous ethanol. Adjust the pH to 5.0 with glacial acetic acid and hydrolyze for 30 minutes. Add the optimized Yellow River sand obtained in step 2 to a horizontal mixer. While stirring, uniformly spray the activation treatment solution onto the sand surface using a misting method. The amount of treatment solution used is 5% of the sand mass. Mix for 15 minutes. Subsequently, dry the material at 80℃ for 2 hours to allow the coupling agent to form chemical bonds on the sand particle surface.
[0108] Step 4: Composite treatment with ultrafine mineral fillers.
[0109] Take 100 parts of the activated Yellow River sand obtained in step 3, add 5 parts of ultrafine fly ash microspheres (particle size ≤ 5 μm) and 0.5 parts of nano SiO2, and mix them in a V-type mixer for 30 min so that the ultrafine mineral particles are uniformly coated on the surface of the Yellow River sand particles, filling the surface micropores and depressions to form a dense composite particle structure.
[0110] III. Preparation method of modified PE fiber: Step 1: Clean the fiber surface.
[0111] High-strength, high-modulus polyethylene fibers with a diameter of 20 μm and a length of 14 mm were selected and immersed in acetone solution. The fibers were then ultrasonically cleaned for 15 minutes in an ultrasonic cleaner to remove residual oil, release agent, and other organic contaminants from the fiber surface. After removal, the fibers were rinsed repeatedly with deionized water 3-5 times and dried in a 60℃ oven until constant weight.
[0112] Step 2: Low-temperature plasma treatment.
[0113] The clean and dry PE fibers obtained in step 1 were evenly laid in the vacuum chamber of the plasma treatment equipment, and the vacuum was evacuated to a background vacuum level of ≤5 Pa. High-purity argon gas was introduced as the working gas, with a flow rate controlled at 80 mL / min, and the vacuum chamber pressure was adjusted to 20 Pa. The radio frequency power supply was turned on and the power was set to 100 W to perform plasma etching treatment on the fibers for 2 min. After the treatment, the fibers were kept under vacuum and cooled for 10 min before being removed for later use.
[0114] Step 3: Chemical grafting modification.
[0115] Take the plasma-activated PE fiber obtained in step 2 and immediately immerse it in the grafting reaction solution for grafting treatment. The grafting reaction solution comprises, by mass, 3 parts acrylic acid, 0.2 parts N,N'-methylenebisacrylamide, 0.2 parts ammonium persulfate, and 90 parts water, with the pH adjusted to 7.0 using a 1 mol / L sodium hydroxide solution.
[0116] Activated PE fibers were added to the grafting reaction solution at a bath ratio of 1:30 (g:mL) and reacted in a constant temperature water bath at 60℃ for 1 h, with slow stirring at 60 r / min during the reaction to ensure uniform grafting. After the reaction was completed, the fibers were removed and washed repeatedly with large amounts of deionized water and ethanol to remove unreacted monomers and homopolymers.
[0117] Step 4: Drying and cutting.
[0118] The grafted modified PE fibers obtained in step 3 were dried in a vacuum drying oven at 60°C until constant weight. The dried fiber bundles were then opened to disperse the fibers into monofilaments, and finally cut to the specified length (12 mm) to obtain the finished modified PE fiber product, which was then sealed and stored in a moisture-proof environment.
[0119] Example 1 This embodiment provides a self-healing, high-toughness concrete, the raw materials for which are prepared by weight parts include: The ingredients are: 35 parts ordinary Portland cement (PO 42.5), 55 parts fly ash, 10 parts silica fume, 45 parts fine aggregate, 25 parts water, 1 part calcium formate, 0.3 parts hydrophobically modified sodium polyacrylate superabsorbent resin, 5 parts VAE latex, 2.0% volumetric content of modified PE fiber, and 0.8% water-reducing agent by mass of cementitious materials (ordinary Portland cement, fly ash, and silica fume).
[0120] The preparation method of self-healing high-toughness concrete includes the following steps: Step 1: Weigh the dry powder according to the ratio. Put all the powder materials into a forced mixer and mix at low speed (mixing shaft speed 20±5 r / min) for 3-5 minutes to make the powder materials evenly mixed.
[0121] Step 2: Mix the polycarboxylate superplasticizer with 80% of the total water volume in advance. During the stirring process, slowly pour the premixed liquid along the cylinder wall. Start the mixer and stir at medium speed (45 r / min) for 3 minutes to form a uniform slurry.
[0122] Step 3: Reserve 20% water for subsequent consistency adjustment, adjusting to a target slump spread of 180 mm. Add water slowly in 2-3 batches, stirring for 30 seconds after each addition, then stop the machine and measure until the target value is reached.
[0123] Step 4: Slowly and evenly sprinkle the weighed modified PE fibers into the slurry obtained in Step 3 in 3-5 batches, with an interval of about 30 seconds between each batch. When adding each batch, spread the fibers evenly back and forth along the axis of the mixer cylinder to avoid fixed-point addition. The amount added in each batch should be limited to the point where no fiber accumulation layer forms on the surface of the slurry. Wait until the fibers of the previous batch have basically sunk below the slurry surface before adding the next batch.
[0124] Step 5: After all the fibers have been added, continue stirring at medium speed (50 r / min) for 2-3 minutes until the fibers are evenly dispersed in the slurry and there are no visible clumps, thus obtaining freshly mixed self-healing high-toughness concrete.
[0125] Step 6: Pour the freshly mixed self-healing high-toughness concrete obtained in Step 5 continuously and uniformly into the mold. Use a layered continuous pouring method, that is, continuously advance from one end of the mold to the other, and do not pour in jumps. Control the free fall height to not exceed 300 mm to avoid fiber segregation caused by impact.
[0126] Step 7: Use a vibrating table or an external vibrator attached to the template for compaction. Control the amplitude to 0.3-0.5 mm and the vibration time to 10-20 seconds to compact the material and remove air bubbles. Closely observe the slurry surface during vibration, and stop immediately when the air bubbles have basically stopped being expelled and the surface is uniformly covered with slurry. Do not use an immersion vibrator, as this will severely interfere with the uniform distribution of fibers.
[0127] Step 8: Use a steel trowel to smooth the surface of the compacted concrete.
[0128] Step 9: Immediately after molding, cover the specimen with plastic film to prevent moisture evaporation. Curing time is 24 hours. The covering should be directly attached to the concrete surface and not suspended in the air. After 24 hours, transfer to water curing or natural curing.
[0129] The compressive strength of the self-healing high-toughness concrete obtained in Example 1 at different ages was tested according to GB / T 50081-2019, and the results are shown in Table 1.
[0130] Table 1 Mechanical properties of self-healing high-toughness concrete
[0131] As shown in Table 1, the self-healing high-toughness concrete material obtained in Example 1 has compressive strengths of 28.6 / 38.2 / 52.4 MPa at 3 / 7 / 28 days, respectively.
[0132] Example 2 This embodiment tests the self-healing high-toughness concrete material obtained in Example 1 to assess its self-repairing ability.
[0133] After curing for 28 days, the self-healing high-toughness concrete material obtained in Example 1 was pre-cracked (introducing a crack with a width of about 100 μm by four-point bending) and placed in a water curing environment (water temperature 20℃) for 28 days. The crack width before and after healing was measured and calculated using formula (1). The results are shown in Table 2.
[0134] (1) In the formula, The width of the healed crack (μm). The crack width (μm) before healing.
[0135] Table 2 Crack Healing Status
[0136] As shown in Table 2, for cracks with an initial crack width of about 102 μm, after 28 days of water curing, the crack width became 18 μm, and the healing rate reached 82.4%.
[0137] Example 3 This embodiment verifies the effect of different amounts of hydrophobically modified sodium polyacrylate water-absorbing resin on the mechanical properties and self-healing properties of concrete.
[0138] Following the baseline formulation of Example 1, six experimental groups were prepared with hydrophobically modified sodium polyacrylate (SPA) at concentrations of 0 parts (blank), 0.1 parts, 0.3 parts, 1.0 parts, 3.0 parts, and 5.0 parts. Unmodified SPA (0.3 parts) served as the control group. Specimens were prepared according to the preparation method in Example 1. After standard curing for 28 days, their compressive strength was tested, and the results are shown in Table 3.
[0139] Table 3 Effect of different admixture dosages on the mechanical properties of mortar
[0140] Table 3 shows that the 28-day compressive strength of the blank group without hydrophobic modified sodium polyacrylate (SPA) was 58.6 MPa, exhibiting the best mechanical properties. Compared with the compressive strength of the mortar specimen with the same amount of superabsorbent polymer (54.2 MPa), the compressive strength of the mortar specimen with hydrophobic modified SPA showed a certain degree of improvement. As the amount of hydrophobic modified SPA increased from 0 to 0.3 parts, the compressive strength decreased slightly (to 52.4 MPa). This is because the low amount of modified superabsorbent polymer has both positive and negative effects within the matrix. Firstly, as cement hydration progresses, the internal relative humidity decreases, and the modified superabsorbent polymer gradually releases the absorbed water, promoting the continuous hydration of the surrounding cement and refining the pore structure. Secondly, after releasing water, the modified superabsorbent polymer leaves a small number of pores within the matrix, which negatively impacts the strength. When the content of hydrophobically modified sodium polyacrylate superabsorbent polymer (SPA) is low, its impact on strength is small. However, as the content of hydrophobically modified SPA increases, the amount of pores it leaves in the matrix increases, and the greater the adverse effect on strength.
[0141] Cracks with a width of less than 100 μm were introduced into each group of specimens using the pre-crack method. The specimens were then placed in a water-curing environment (water temperature 20℃) for 28 days. The crack width before and after healing was measured and the crack healing rate was calculated. The results are shown in Table 4.
[0142] Table 4. Effect of different admixture dosages on the self-healing properties of mortar
[0143] As shown in Table 4, the crack healing rate of the blank group without hydrophobic modified sodium polyacrylate (SPA) was only 35.2%, mainly relying on the continuous hydration of the cement matrix itself to achieve a small amount of crack filling. As the dosage of SPA increased from 0 to 0.3 parts, the crack healing rate significantly increased to 82.4%. When the dosage was further increased to 1.0 part, the healing rate reached a peak of 87.4%, indicating that the internal curing moisture provided by the SPA was sufficient to support the full formation of hydration products at the crack interface. When the dosage increased to 3.0 and 5.0 parts, the healing rate decreased to 85.7% and 78.6%, respectively. This was mainly because the excessive pores of the SPA weakened the effective area available for hydration product deposition at the crack interface and reduced the strength of the matrix itself. When the amount of water-absorbing resin is 0.3 parts, the crack healing rate of the unmodified sodium polyacrylate is 77.0%, which is lower than the crack healing rate of 82.4% of the hydrophobically modified sodium polyacrylate water-absorbing resin, and the strength is higher than that of the modified water-absorbing resin.
[0144] Taking into account both mechanical property retention and self-healing efficiency, the present invention preferably uses 0.1-3.0 parts of hydrophobic modified polyacrylic acid water-absorbing resin, more preferably 0.3-1.0 parts. Within this range, the 28-day compressive strength is ≥42.3 MPa and the crack healing rate is ≥82.4%, which can meet the dual requirements of hydraulic structures for material load-bearing capacity and self-repair function.
[0145] Example 4 This embodiment verifies the combined effects of different modified PE fiber dosages on the mechanical properties and crack healing behavior of concrete.
[0146] Following the baseline formulation of Example 1, six experimental groups were established with modified PE fiber volume fractions of 0% (blank group), 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%. Unmodified PE fiber (2.0%) served as the control group. Specimens for each group were prepared according to the preparation method of Example 1. The 28-day compressive strength of each group of specimens was tested according to GB / T 50081-2019. Four-point bending tests were conducted according to ASTM C1609 / C1609M-10 to determine the ultimate flexural strength and ultimate tensile strain of each group of specimens. Simultaneously, the 28-day crack healing rate of each group of specimens was determined according to the method of Example 2 (initial crack width controlled at 100±15 μm). The results are shown in Table 5.
[0147] Table 5. Effects of different modified PE fibers on the mechanical properties and crack healing rate of mortar.
[0148] As shown in Table 5, the blank group without modified PE fibers exhibited typical brittle fracture characteristics, with an ultimate tensile strain of only 0.06% and the lowest crack healing rate (36.5%). This indicates that although the pure matrix material possesses a certain self-healing ability, its crack width control is poor, with large and continuous single cracks, which is not conducive to crack self-healing. As the fiber volume content increased from 0 to 2.0%, the ultimate flexural strength and ultimate tensile strain continuously increased, reaching 13.6 MPa and 3.2%, respectively, reflecting the multi-crack cracking and stress bridging effect of modified PE fibers. Simultaneously, the crack healing rate increased from 52.3% to 82.4%. This is because the fiber bridging effect disperses a single wide crack into multiple micro-cracks, providing a larger specific surface area and a shorter healing material transport path, which is beneficial for the filling and bonding of hydration products.
[0149] However, when the fiber content is too high (2.5%), the compressive strength and crack healing rate of the mortar specimens decrease. This is because the excessive fiber content leads to insufficient film thickness of the mortar coating the fibers, an increase in defects at the fiber-matrix interface, and some fibers fail to fully play their bridging role, resulting in a weakening effect when pulled out. At the same time, the increased porosity inside the matrix also weakens the material basis for crack healing.
[0150] Taking into account mechanical properties, self-healing efficiency and economic cost, the present invention preferably uses 1.0-2.5% modified PE fiber volume fraction, and more preferably 1.5-2.0%.
[0151] Example 5 This embodiment provides a self-healing, high-toughness concrete, the raw materials for which are prepared by weight parts include: The ingredients are: 120 parts ordinary Portland cement, 60 parts fly ash, 60 parts silica fume, 120 parts fine aggregate, 60 parts water, 10 parts calcium formate, 3 parts hydrophobically modified polyacrylic acid water-absorbing resin, 20 parts dispersible latex, 2.5% modified PE fiber by volume, and 1.0% water-reducing agent by mass of cementitious materials (ordinary Portland cement, fly ash, and silica fume).
[0152] The preparation method of self-healing high-toughness concrete is the same as in Example 1.
[0153] Comparative Example 1 This comparative example provides a self-healing high-toughness concrete. Compared with Example 1, the difference is that the fine aggregate does not contain nano-SiO2, while the remaining components and preparation method are the same as in Example 1.
[0154] Comparative Example 2 This comparative example provides a self-healing high-toughness concrete. Compared with Example 1, the difference is that the fine aggregate does not contain ultrafine fly ash microspheres (particle size ≤ 5 μm), while the remaining components and preparation method are the same as in Example 1.
[0155] Comparative Example 3 This comparative example provides a self-healing high-toughness concrete. The difference between this example and Example 1 is that "Step 3: Surface activation treatment" was not performed during the preparation of the fine aggregate. The remaining components and preparation methods are the same as in Example 1.
[0156] The 28-day compressive strength of specimens in Example 5 and Comparative Examples 1-3 was tested according to GB / T 50081-2019. Four-point bending tests were conducted according to ASTM C1609 / C1609M-10 to determine the ultimate flexural strength and ultimate tensile strain of each group of specimens. Simultaneously, the 28-day crack healing rate of each group of specimens was determined according to the method in Example 2 (initial crack width controlled at 100±15 μm). The results are shown in Table 6.
[0157] Table 6 Mechanical properties and crack healing rate of specimens
[0158] As shown in Table 6, Example 5 significantly outperformed the comparative examples in terms of 28-day compressive strength (52.1 MPa), ultimate flexural strength (14.2 MPa), ultimate tensile strain (3.8%), and crack healing rate (79.6%). Comparative Example 1, lacking nano-SiO2, suffered from a deficiency in pozzolanic activity and micro-aggregate filling effect, resulting in the largest decrease in compressive strength and crack healing rate, decreasing by 17.8% and 14.3% respectively compared to Example 5. Comparative Example 2, lacking ultrafine fly ash microspheres, experienced reduced slurry fluidity, leading to uneven fiber dispersion, and all properties were lower than Example 5. Comparative Example 3, due to the lack of surface activation treatment on fine aggregates, suffered from insufficient aggregate-slurry interfacial bond strength, resulting in lower mechanical properties and healing rate compared to Example 5. These results indicate that the synergistic introduction of nano-SiO2 and ultrafine fly ash microspheres, along with surface activation treatment of fine aggregates, jointly improved the compactness, fiber dispersion, and interfacial bonding performance of concrete, thereby endowing the material with excellent self-healing ability and high toughness.
[0159] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A self-healing, high-toughness concrete material, characterized in that, The raw materials for preparation, by mass parts, include: 30-120 parts silicate cement, 30-60 parts fly ash, 10-60 parts silica fume, 0.1-3 parts water-absorbing resin, 2-20 parts latex, 1-10 parts calcium formate, 40-120 parts fine aggregate, 25-60 parts water, PE fiber, water-reducing agent. The volume of PE fibers is 0.5-2.5% of the volume of self-healing high-toughness concrete materials; The water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume.
2. The self-healing high-toughness concrete material as described in claim 1, characterized in that, The water-absorbing resin is a hydrophobically modified polyacrylic acid water-absorbing resin; The preparation method of the hydrophobically modified polyacrylic acid water-absorbing resin includes: The polyacrylic water-absorbing resin was dried until its moisture content was less than 0.5%. Prepare a crosslinking agent solution, spray the crosslinking agent solution onto the surface of polyacrylic acid water-absorbing resin, stir, and react at 800-100℃ for 1-2 h to obtain surface crosslinked modified water-absorbing resin; Prepare a hydrophobic modification solution, spray the hydrophobic modification solution onto the surface of the cross-linked modified water-absorbing resin, stir, and dry to obtain a hydrophobic modified polyacrylic acid water-absorbing resin. The particle size of the polyacrylic acid-based water-absorbing resin is 80-150 mesh; The crosslinking agent solution comprises, by weight, 0.5-2.0 parts of ethylene glycol diglycidyl ether, 10-20 parts of water, and 5-10 parts of anhydrous ethanol; the mass ratio of the crosslinking agent solution to the polyacrylic acid superabsorbent resin is 15.5-32:
100. The hydrophobic modification solution comprises, by mass parts: 1-3 parts calcium stearate, 20-40 parts anhydrous ethanol, and 5-10 parts water; the mass ratio of the hydrophobic modification solution to the polyacrylic acid-based water-absorbing resin is 26-53:
100. The hydrophobic modified polyacrylic acid water-absorbing resin has a particle size of less than or equal to 0.15 mm.
3. The self-healing high-toughness concrete material as described in claim 1, characterized in that, The latex includes vinyl acetate-ethylene copolymer.
4. The self-healing high-toughness concrete material as described in claim 1, characterized in that, By weight, the fine aggregate comprises: 100 parts activated modified Yellow River sand, 3-8 parts fly ash microspheres, and 0.5-1.0 parts nano-silica; the particle size of the fly ash microspheres is ≤5 μm; The preparation method of the activated modified Yellow River sand includes: Prepare a surface activation treatment solution, spray the surface activation treatment solution onto the surface of Yellow River sand, stir, and dry to obtain the product; The particle size distribution of the Yellow River sand includes 0.075-0.3 mm accounting for 15-25%, 0.3-0.6 mm accounting for 30-40%, 0.6-1.18 mm accounting for 25-35%, and 1.18-2.36 mm accounting for 5-15%, by mass percentage. The surface activation treatment solution comprises, by weight, 0.5-1.5 parts of silane coupling agent, 30-50 parts of water, 50-70 parts of anhydrous ethanol, and a pH of 4.0-5.
0. The amount of surface activation treatment solution used is 2-5% of the mass of Yellow River sand.
5. The self-healing high-toughness concrete material as described in claim 4, characterized in that, The method for preparing the fine aggregate includes: mixing activated modified Yellow River sand, fly ash microspheres and nano silica for 30-40 min, and coating the fly ash microspheres and nano silica on the surface of the activated modified Yellow River sand with silane coupling agent to form a composite particle structure.
6. The self-healing high-toughness concrete material as described in claim 1, characterized in that, The PE fiber is a modified PE fiber; The method for preparing the modified PE fiber includes: Select polyethylene fibers with a diameter of 20-40 μm and a length of 12-18 mm, clean the surface, dry, and set aside. The cleaned and dried polyethylene fibers were subjected to plasma etching to obtain plasma-activated polyethylene fibers. A grafting reaction solution was prepared, and plasma-activated polyethylene fibers were immersed in the grafting reaction solution to carry out the reaction. After the reaction was completed, the fibers were removed, washed, and dried to obtain modified PE fibers. The plasma etching process includes: evacuating to a vacuum level ≤ 5 Pa, introducing argon gas as the working gas at a flow rate of 50-100 mL / min, and adjusting the vacuum chamber pressure to 20-50 Pa; turning on the radio frequency power supply and setting the power to 100-200 W, and performing plasma etching on the cleaned and dried polyethylene fiber for a processing time of 2-8 min; after the processing is completed, maintaining the vacuum state and cooling for 10-15 min, and then removing the fiber for later use. The grafting reaction solution comprises, by mass parts: 3-8 parts acrylic acid, 0.1-0.3 parts N,N'-methylenebisacrylamide, 0.2-0.5 parts ammonium persulfate, and 90-96 parts water, with a pH of 6.0-7.0; The process of immersing plasma-activated polyethylene fibers in a grafting reaction solution includes: adding plasma-activated polyethylene fibers to the grafting reaction solution and reacting at 60-80°C for 1-3 hours, during which time the mixture is stirred at a speed of 60-80 r / min; after the reaction is completed, the fibers are removed, washed, dried, loosened, and slit to obtain modified PE fibers. The modified PE fiber has a length of 12-18 mm.
7. The self-healing high-toughness concrete material as described in claim 1, characterized in that, The raw materials for preparation, by mass parts, include: The composition includes: 30-40 parts silicate cement, 50-60 parts fly ash, 10-20 parts silica fume, 0.1-3 parts water-absorbing resin, 2-10 parts latex, 1-5 parts calcium formate, 40-50 parts fine aggregate, 25-30 parts water, PE fiber, and water-reducing agent; the volume of PE fiber is 1.0-2.5% of the volume of the self-healing high-toughness concrete material; the mass of the water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume. Alternatively, the raw materials for preparation, by mass parts, include: The ingredients are: 30-40 parts silicate cement, 50-60 parts fly ash, 10-20 parts silica fume, 0.3-1 part water-absorbing resin, 2-10 parts latex, 1-5 parts calcium formate, 40-50 parts fine aggregate, 25-30 parts water, PE fiber, and water-reducing agent; the volume of PE fiber is 1.5-2.0% of the volume of self-healing high-toughness concrete material; the mass of water-reducing agent is 0.5-1.0% of the total mass of silicate cement, fly ash, and silica fume.
8. A method for preparing the self-healing high-toughness concrete material according to any one of claims 1-7, characterized in that, include: Silicate cement, fly ash, silica fume, water-absorbing resin, latex, calcium formate, and fine aggregate are mixed to obtain a mixed dry material; Mix the water-reducing agent with 80-90% of the total water volume and then add it to the mixed dry material. Stir well to obtain the slurry. Adjust the slump spread of the slurry to 150-250 mm with the remaining water, add PE fibers in batches, and stir to obtain a self-healing high-toughness concrete material.
9. The preparation method according to claim 8, characterized in that, Silicate cement, fly ash, silica fume, water-absorbing resin, latex, calcium formate, and fine aggregate are mixed at a speed of 20±5 r / min for 3-5 min to obtain a mixed dry material; Mix the water-reducing agent with 80-90% of the total water volume and add it to the mixed dry material. Stir at 45-60 r / min for 2-3 min to obtain the slurry. Adjust the slump spread of the slurry to 150-250 mm with the remaining water, add PE fibers in batches and stir. After all the PE fibers have been added, stir at a speed of 45-60 r / min for 2-3 min to obtain a self-healing high-toughness concrete material. The resulting self-healing high-toughness concrete material was poured, compacted by vibration, and then cured after surface polishing.
10. The application of the self-healing high-toughness concrete material according to any one of claims 1-7 in the repair of cracks in hydraulic structures.